Numerical modeling and validation for 3D coupled-nonlinear thermo-hydro-mechanical problems in masonry dams. (1st January 2017) - Nguyen-Tuan, Long; Könke, Carsten; Bettzieche, Volker; Lahmer, Tom
Highlights: We introduce a coupled thermo-hydro-mechanical model for masonry materials. A series of 3D numerical simulations are carried out considering several scenarios. Validation with measurements: temperature, displacement, stress and pore pressure. Improvement of computational cost using parallel computation. Abstract: We introduce in this article a fully coupled thermo-hydro-mechanical (THM) model describing the physical phenomenon present in masonry materials. A series of 3D numerical simulations are carried out for the THM analysis of a dam during its impounding process. The results of the coupled THM analyzes are validated with measurements recorded during that process in terms of transient displacement, pore-water pressure and temperature values. An agreement between numerical simulations and measured data proves that the coupled THM model can well reproduce the multi-physical behavior of masonry dams. Furthermore, we introduce herein a solution for a large system of balance equations by combining parallel computation, storage in Compressed Sparse Row format, and iterative pre-conditioned Conjugate Gradient Squared method in order to improve the computational cost.